PENGARUH RETURN ON ASSET, RETURN ON EQUITY, EARNING PER SHARE, DEBT TO EQUITY RATIO, DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM (Studi pada Perusahaan yang Tergabung dalam Jakarta Islamic Index) - Puspita, Ismi Karima Tri; Indrawati, Nur Khusniyah (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
Investing on sharia stock is a good alternative for funding management because sharia stocks are far away from business which classified as illegitimate business according to Islam. Jakarta Islamic Index (JII) used as a benchmark in measuring performance of a stock investment which based on sharia. This research aims to examine the value relevance of accounting information in explaining stock price. This research used Return on Asset, Return on Equity, Earning per Share, Debt to Equity Ratio, and Price to Book Value as proxies of accounting information. The sample of this research was all the company which listed in JII for five times consecutively from 2007 until 2011. This research was explanatory research, which explain the existence of effect between the dependent and independent variables through a hypothesis testing. The result showed that ROE, EPS, and PBV have significant influence on stock price, while ROA and DER have no significant influence on the stock price of companies listed in JII. Although it is a small sample size, some relevant changes and modifications can be included in future research to obtain better result.Keywords: Return on Asset, Return on Equity, Earning per Share, Debt to Equity Ratio, Price to Book Value, Stock Price, Jakarta Islamic Index